2021
DOI: 10.2147/jbm.s329360
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ABO and Rhesus Blood Group Phenotypes Among Blood Donors at Bahir Dar Blood Bank, Amhara, Northwest Ethiopia: A Retrospective Cross-Sectional Study

Abstract: Background Among the blood group antigens identified, ABO and Rhesus are the most important in transfusion medicine. ABO blood group antigens are the most immunogenic followed by Rhesus (D antigen). These blood groups’ frequency distribution varies among different regions and races of the world. This study aimed to identifying the frequency distribution of ABO blood group and rhesus factors among blood donors in Ethiopia. Methods and Materials Aretrospective cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 20 publications
6
15
1
Order By: Relevance
“…In contrast, this study’s finding was higher than a study conducted in Bangladesh, 19 India, 23 Nigeria, 21 , 22 , 26 Uganda, 6 and Niger 21 which ranged from 1.2% to 6.55%. In contrast, this study is lower than a study conducted in India, 18 and different parts of Ethiopia (Woldia, 16 Gambella, 14 and Bahirdar 10 ) showed that 8.9%, 39.86%, 19.37%, and 8.5% were Rh-D negative, respectively. Further, in this study, the Rh-D negative blood group in Gondar, Debre-Markos, Bahir Dar, and Dessie districts was 9.6% (24/250), 4.46% (12/269), 8.59% (26/303), and 7.5% (16/214), respectively.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…In contrast, this study’s finding was higher than a study conducted in Bangladesh, 19 India, 23 Nigeria, 21 , 22 , 26 Uganda, 6 and Niger 21 which ranged from 1.2% to 6.55%. In contrast, this study is lower than a study conducted in India, 18 and different parts of Ethiopia (Woldia, 16 Gambella, 14 and Bahirdar 10 ) showed that 8.9%, 39.86%, 19.37%, and 8.5% were Rh-D negative, respectively. Further, in this study, the Rh-D negative blood group in Gondar, Debre-Markos, Bahir Dar, and Dessie districts was 9.6% (24/250), 4.46% (12/269), 8.59% (26/303), and 7.5% (16/214), respectively.…”
Section: Discussioncontrasting
confidence: 87%
“…This study is similar to a study conducted in Bahir-Dar. 10 “O” Rh-D positive and “A” were the first two dominant blood groups, while “AB” Rh-D negative and “O” Rh-D negative were the least dominant blood types among blood donors. In contrast to this, a study conducted in India 23 and Pakistan 24 , 25 showed that “B” positive was the dominant blood group followed by the “O” positive blood group.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The ABO blood groups were the first human blood group system, discovered by Karl Landsteiner in 1900 [1]. Based on the presence of antigens on the surface of RBC, individuals are classified into four major blood groups (A, B, AB, and O) [2].…”
Section: Introductionmentioning
confidence: 99%